A night soil collection point: the public toilets in Hong Kong, 1860s-1920s. Issue 2 (3rd October 2016) - Chong, Yuk-sik
Abstract : Purpose: This paper aims to understand the implication of night soil selling at the public toilets for the shared interests between colonial state and business in nineteenth-century Hong Kong. More specifically, this paper attempts to look at the ways the toilets were sustained by the sharing interests over night soil profits between state and business sector. Design/methodology/approach: It is argued from the political economy perspective that the night soil profit determined the public toilet development. Findings: The successful emergence of the modern state of colonies was generally attributed to colonial modernization, a force that was widely recognized for having introduced hygienic modernity. It was easily assumed that the public toilets would be provided by colonial government. Instead, sanitary problems during the early colonization of this colony were addressed by the privately-owned public pail toilets provided by big Chinese landowners through the selling of night soil. Based on this quasi-commercial mode, these toilets, which served as night soil collection points, were certainly inefficient; they however survived for half a century into the early twentieth century. Originality/value: The paper challenges the long-established assumptions of binary relations and hierarchical public roles that put them into zero-sum competition of capacity. It rather argues that the interests aligned with each other.